Development of Science Learning Media Klanimal Android-Based for Elementary School Students - Fadhilah Nur Lailatus Saadah; Fitria Nur Hasanah (research, training and philanthropy institution Natural Aceh, 2023)
The difficulties students face in understanding the concepts of Science are due to their abstract nature, making it difficult to retain long-term memory. The research objective is to develop an interactive Android-based media to visualize Science learning, specifically the concept of animal classification based on their types of food, to facilitate its retention in students' long-term memory. The